Immediate effect of recurrent laryngeal nerve stimulation in patients with idiopathic unilateral vocal fold paralysis. - Yan, Jing; Hou, Jin; Zhang, Huihui; Yang, Xinyi; Sheng, Ying; Du, Xiaoying; Kong, Demin; Wang, Zhenghui; Ren, Xiaoyong; Wu, Liang (Acta Oto-Laryngologica, 2024)
There is a lack of effective treatment for idiopathic unilateral vocal fold paralysis (IUVFP). A better phonation was reported by patients after laryngeal nerve stimulation during our clinical examination. This study aims to investigate immediate effect of recurrent laryngeal nerve (RLN) stimulation on phonation in patients with IUVFP. Sixty-two patients with clinically identified IUVFP underwent RLN stimulation with needle electrodes. Laryngoscopy, acoustic analysis, and voice perception assessment were performed for quantitative comparison of vocal function and voice quality before and after the intervention. Laryngoscopic images showed a larger motion range of the paralyzed vocal fold (p <.01) and better glottal closure (p <.01) after RLN stimulation. Acoustic analysis revealed that the dysphonia severity index increased significantly (p <.01) while the jitter and shimmer decreased after the intervention (p <.05). According to perceptual evaluation, RLN stimulation significantly increased RBH grades in patients with IUVFP (p <.01). Furthermore, the improvement in voice perception had a moderate positive correlation with the decrease in the glottal closure. This study shows a short-term improvement of phonation in IUVFP patients after RLN stimulation, which provides proof-of-concept for trialing a controlled delivery of RLN stimulation and assessing durability of any observed responses.